Maritime logistics and economic growth in the context of APEC: a two-stage data envelopment analysis study - Odette Delfin-Ortega (Journal of Shipping and Trade)
Abstract The objective of this research is to analyze the factors influencing port efficiency from 2000 to 2023 using data envelopment analysis methodology and a dynamic ordinary least squares econometric model. In the first phase, the evaluation of port efficiency revealed an average score of 52%; with 10 ports showing high efficiency and two ports with efficiency below 1%. The results indicated the need for strategies to improve port efficiency in the region as enhancing infrastructure, streamlining processes, and improving logistics. In the second phase, Gross domestic product (GDP) per capita, the economically active population, and connectivity were used as independent variables to examine their impact on efficiency. The dynamic ordinary least squares model revealed that GDP per capita is the most influential factor in port efficiency, followed by maritime connectivity. These findings suggest that economic capacity and logistic networks are fundamental for improving port efficiency. On the other hand, the economically active population had a lesser impact, highlighting the importance of having a highly skilled workforce. The research concludes that it is crucial for port authorities to invest in infrastructure and human capital development to achieve more efficient and competitive ports. These efforts should focus on improving connectivity and promoting economic growth, which is essential for the sustainable development of the port sector.